EFFECT OF NOSTRIL BREATHING ON BLOOD PRESSURE IN HYPERTENSION PATIENTS - Syapitri, Henny; Siregar, Laura Mariati; Sinurat, Lasma Rina Efrina (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Hypertension other resulted number death which tall also impact on expensive treatment and care that must be borne by the sufferer. It should be noted that hypertension has an impact on decline quality of human life. If you have high blood pressure however no quick done treatment and control in a manner regular then what happens is that it will have an impact in even serious cases death. Nostril breathing technique is breathing by closing one hole nose in a manner alternate. Nostrils breathing tehnique own benefit that is can strengthen whole system respiratory, overcome stress, lower pressure blood. The purpose of this study was to identify the effect of nostril breathing on blood pressure. This type of research is a quasy experiment using the pre and posttest method without a control group design. The sample in this study was 20 people using a purposive sampling technique. The aspect to be measured in this study is blood pressure. The data obtained from the measurement results twice, namely blood pressure before and after the intervention was given. Statistical analysis used in this study is to use paired t-test. The results showed that the average blood pressure analysis before the nostril breathing intervention was given was (mean : 150.50) , and the average value after the intervention was given (mean : 139.00). The results of the analysis of the effect of nostril breathing on blood pressure using the paired t-test obtained a value of p = 0.000 (p <0.05 ) . Data analysis showed that there were significant differences between blood pressure before and after the intervention.